Eco-friendly Hospitality in Himalayas: An Investigation on Homestay Services in India - Aruditya Jasrotia; Parvinder Kour (ASEAN Journal on Hospitality and Tourism, 2022)
The hospitality sector has been considered as an equal contributor to tourism impacts. As far as the sustainable destination development is concerned, there requires a balanced approach by the authorities for economic benefits and the benefits to the environment. Where the concept of homestays is attaining is popularity among tourists, the realization for its contribution to economic development to the local population is also important along with keeping in view that these hospitality services are aligned with eco-friendly practices, thereby reflecting upon the sustained life of the Himalayan tourism. Hence, the present study was conducted to inspect the part of home stay practices in local socio-economic growth of people and to examine if these practices are aligned with environmental safety. The study has been conducted in various regions of Uttarakhand, Himachal Pradesh and Sikkim. The study revealed a requirement for the awareness and increase in knowledge among the homestay authorities for adopting the sustainable hospitality practices in regular service operations along with considering its benefits for local economic development.